Analysis of creep behavior of welded joints of P91 steel at 600 °C. (March 2019) - El-Desoky, O.E.; Abd El-Azim, M.E.; ElKossy, M.R.
Abstract: The martensitic P91 steel (9Cr-1Mo-V-Nb) has been developed for ultra-supercritical pressure application in steam power plants. The creep rupture strength of the welded joint of this steel is limited by the fine-grained region of its heat affected zone (HAZ). The factors which result in the reduction of the creep rupture strength of the fine-grained region of HAZ were discussed. It was found that the most effective factor reducing the creep rupture strength of the fine-grained region of the HAZ of the welded joint of P91 steel, in comparison with other regions of the welded joint, is the finer prior austenite grain size. These fine prior austenite grains of the fine-grained region of the HAZ accelerate the rate of growth of martensite lath subgrains which results in a softer martensite matrix. The minimum creep rate dependence on applied stress for base metal, welded joints and the samples simulating the fine-grained region of the welded joints was described by means of the conventional power-law equation. The experimental results, both in the form of strain versus time creep curves and of minimum creep rate versus time creep curves were used to study the creep behavior of the welded joints of P91 steel at 600 °C. Highlights: P91 steel has been used for the main steam pipes headers and boilers in fossil fuel power generation plants. The creep rupture strength of its welded joints is limited by the fine – grained heat affected zone. The fine prior austenite grain size of this region accelerates the rate of growth of martensitic lath subgrains which results in softer martensite matrix. The creep strength of P91 steel is limited by the FGHAZ of welded joint and its mechanism at 600 °C and stress 70–150 MPa is dislocation creep.